Breathing life into Classics: the Utopic Task of Translating Aristophanes (El Hilo de la Fabula, 2022)
In this paper we aim to reflect on general issues in the translation of ancient classical texts, particularly Greek theater -given their nature as scripts intended for the stage-. At the same time, based on our experience as translators of Aristophanes, as well as on the testimonies of other translators of the same author, we will point out a series of difficulties -not exhaustive-, when transposing the Aristophanic language into Spanish, including, puns, speaking names, obscene lexicon, colloquialisms, mentions to the events and characters of his time.
Keywords: Aristophanes; Ancient Comedy; Translation